Biogeneration of activated carbon in the treatment of phenolic compounds - Aktaş, Özgür. (Thesis (Ph.D.)-Bogazici University. Institute of Environmental Sciences, 2006., 2006)
This study aimed to clarify the effect of adsorbability, desorbability, biodegradability and activated carbon type on the extent of bioregeneration in the treatment of phenolic compounds in activated sludge systems combined with activated carbon. Bioregenerabilities of activated carbons preloaded with phenol, 2-chlorophenol and 2-nitrophenol were studied. For this purpose, four different activated carbon types; thermally activated and chemically activated powdered carbons (PAC), and their granular countertypes (GAC) with similar physical characteristics were used. Thermally activated carbons were better adsorbers for phenolic compounds than chemically activated ones. However, apparently higher adsorption irreversibility was calculated in the case of thermally activated carbons. The results suggested that, rather than the physical form, carbon activation type and chemical surface characteristics played a more important role on adsorbability of phenolic compounds and its reversibility. Also, adsorption and its reversibility were highly dependent on the type of the target compound. Bioregeneration of chemically activated carbons was also higher than thermally activated ones. This showed that bioregeneration was controlled by the reversibility of adsorption. The results suggested that carbon activation type was of crucial importance for bioregeneration. PAC and GAC countertypes showed comparable bioregeneration efficiencies indicating that carbon size was not an effective factor. Oxidative polymerization of phenol and 2-chlorophenol was a plausible explanation for lesser bioregeneration of thermally activated carbons. However, bioregeneration efficiencies of thermally activated carbons were much higher than their total desorbabilities. This indicated the presence of exoenzymatic bioregeneration. Bi-solute experiments showed that competition for adsorption sites greatly determined the extent of adsorption reversibility and bioregeneration. Cometabolic biodegradation of 2-chlorophenol and 2-nitrophenol in the presence of phenol resulted in efficient bioregenerability of activated carbons, when they were loaded with non-growth substances together with a growth substrate.
Keywords: Carbon, Activated.; Biodegradation.; Adsorption.